Medieval Wildernesses and King Lear: Heath, Forest, Desert. (2nd July 2016) - Steffes, Michael
Abstract : In Shakespeare's King Lear, the impact of the storm on the heath on Lear is best explained in light of two obsolescent medieval cultural traditions that found positive value in wild nature, in contrast to the negative views common in early modern England. The forest laws help us understand the heath as a place, as well as the monarch's relationship to that place. But for understanding the inner change in Lear, which is like that of the knight-hermits in medieval romance, we must turn to the cultural roots of the eremitical tradition in monastic spirituality, which, as Jacques Le Goff has argued, were transplanted from the deserts of Egypt to the forests of France and England. These two medieval cultural traditions, transposed into the play's ancient pagan setting, provide essential help in understanding why a violent storm in a bleak landscape has such a strong presence in Shakespeare's great tragedy.